PENINGKATAN IBU HAMIL DALAM PENCEGAHAN ANEMIA DEFISIENSI BESI (ADP) DAN KEK DI KELAS PRENATAL WILAYAH KERJA PUSKESMAS KANOR - Fitria Rizky; Niken Yuli Astuti (Jurnal Humanis ( Jurnal Pengabdian Masyarakat ISTeK ICsada Bojonegoro), 2023)
Anemia generally occurs throughout the world, especially in developing countries and in low socio-economic groups. In the adult group anemia occurs in women of reproductive age, especially pregnant women and lactating women because they experience a lot of iron deficiency. Nearly all of these deaths were due to a lack of knowledge resources, and most were preventable. It is generally caused by iron deficiency, so it is better known as anemia. Furthermore, anemia will occur when the mother's hemoglobin levels fall to below 11gr/dl during the third trimester. Based on the 2021 Indonesian Health Profile, MMR has decreased in relation to pregnancy, childbirth and postpartum by 359 per 100,000 live births and the Neonatal Mortality Rate (AKN) has also decreased in 2020 by 19 per 1,000 live births. The method for implementing the Community-Based Hypertension Control Program is as follows: 1) Planning stage which includes: by forming a team, collecting data which includes: general data, special data, health profile, survey results, analyzing the situation: internal and external problems, determine program targets and indicators. 2) Pre-implementation stage by carrying out feasibility and suitability tests of the assessment format and observation sheets that will be used as the basis for implementing the program. 3) Program Implementation Stage: carry out early detection and monitoring of anemia in pregnant women, 4) Target: cadres, community activists, village midwives/nurses, lecturers and students, Target: pregnant women. 5) Evaluation Stage: using the Early Detection and Prevention of Anemia form. The community service program which combines education, mentoring, and a social support system is expected to increase knowledge and attitudes towards preventing anemia and complications of anemia in pregnant women. Of the 28 participants who took part, it was necessary to increase the knowledge of pregnant women, especially preventing anemia, so that they could control and change their lifestyle to be healthier.